Dialektika Khilafah dan Politik Kebangsaan dalam Media Publik Siber - Minan Jauhari; Yayan Sakti Suryandaru; Rachma Sugihartati (UIN Sunan Gunung Djati Bandung, 2021)
The current article discusses the dialectic of Khilafah (caliphate) and the national political system expressed through two cyber media of two religious communities as the new public spaces, namely the da'wah media of Islam Kaffah community and NU community. The current debate/discourse explains Khilafah (Caliphate), which is an Islamic teaching that must be applied to Muslims. On the other hand, it is understood as a historical fact because it contrasts with the Indonesian national political system. This study is qualitative research with an ethnomethodological method focusing on digital conversation to be analyzed. Such analysis is conducted by displaying texts which show a conversational activity in conveying arguments and ideas about the Khilafah (caliphate) and national political system as the data analysis. The aim is to answer the research question about how the dialectic of Khilafah (caliphate) and national political system is portrayed through the new public spaces (cyber media), whether the dialectic processes that occur produce consensus or instead of trigger conflicts. Furthermore, by using a social perspective that uses the term